2016
DOI: 10.1124/jpet.115.230706
|View full text |Cite
|
Sign up to set email alerts
|

A Soluble Guanylate Cyclase Activator Inhibits the Progression of Diabetic Nephropathy in the ZSF1 Rat

Abstract: Therapies that restore renal cGMP levels are hypothesized to slow the progression of diabetic nephropathy. We investigated the effect of BI 703704, a soluble guanylate cyclase (sGC) activator, on disease progression in obese ZSF1 rats. BI 703704 was administered at doses of 0.3, 1, 3, and 10 mg/kg/d to male ZSF1 rats for 15 weeks, during which mean arterial pressure (MAP), heart rate (HR), and urinary protein excretion (UPE) were determined. Histologic assessment of glomerular and interstitial lesions was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 28 publications
(25 reference statements)
3
40
2
1
Order By: Relevance
“…It is important to note that the dose of enalapril used in our study is estimated to be roughly 3-10-fold over the clinically relevant dose. This high dose leads to profound hemodynamic effects (Boustany-Kari et al 2016) that are likely the primary mechanism for the immediate drop in proteinuria and the improvement in GFR observed throughout the study. In contrast, ZSF1 rats treated with MK-0429 display late onset reduction in proteinuria 2017 | Vol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the dose of enalapril used in our study is estimated to be roughly 3-10-fold over the clinically relevant dose. This high dose leads to profound hemodynamic effects (Boustany-Kari et al 2016) that are likely the primary mechanism for the immediate drop in proteinuria and the improvement in GFR observed throughout the study. In contrast, ZSF1 rats treated with MK-0429 display late onset reduction in proteinuria 2017 | Vol.…”
Section: Discussionmentioning
confidence: 99%
“…This high dose leads to profound hemodynamic effects (Boustany‐Kari et al. ) that are likely the primary mechanism for the immediate drop in proteinuria and the improvement in GFR observed throughout the study. In contrast, ZSF1 rats treated with MK‐0429 display late onset reduction in proteinuria suggesting that the underlying mechanism is likely independent of hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, high dose angiotensin-converting enzyme (ACE) inhibitor Enalapril normalized blood pressure, prevented renal fibrosis, and virtually eliminated albuminuria. A supramaximal dose of Enalapril was used because several studies in humans have indicated that tissue protection by renin-angiotensin-aldosterone system (RAAS) inhibitors requires doses much higher than needed to normalize blood pressure [11, 41, 42]. Thus, clinical observations seen with Rosiglitazone and Enaplapril are largely recapitulated in obese ZSF1 rats.…”
Section: Discussionmentioning
confidence: 99%
“…While the disease progresses, several other renal mediators, such as angiotensin II, AGEs, transforming growth factor (TGF)-b, and protein kinase C (PKC), further increase the activity of NOX enzymes, resulting in a further aggravated renal damage [14]. Impaired cGMP signaling by ROS uncoupling of NOS3 and oxidizing sGC (Figure 1) may further aggravate tubulointerstitial damage and fibrosis [39].…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%